The Philosophy of Supplication in Sufism and Answers of Misconception - Al-Ta'an, Ahmad Idrees (Journal of Islamic and Religious Studies, 2021)
This research deals with the question of supplication among the people of Sufism in terms of the truth of supplication, its importance, how Sufis understand it, and the relationship of supplication to faith in general. It is through their own philosophy of understanding supplication that a person can find comfortable answers to the doubts raised by skeptics about supplication in terms of its answer, the benefit of it, and how does the appointed person deal with the supplication in its different situations? And what is his position - as a servant of God Almighty - regarding his seeing the supplication answered sooner, or his failure to see that? Sufism sparks in their philosophy through a fundamental issue that is the basis for all other issues, i.e; the reality of the human being, his identity, the essence of this identity, the reality of this worldly life, its purpose, and the position of man in it. If a person understands this correctly, then all the other issues are easy to understand for the mind, and the heart which always needs to be monitored and addressed in order not to lose sight from the greater purpose, remains on the right path. Thus, Sufis believe that dealing with any suspicions related to faith and supplication is dealt with in two ways: the first is the understanding of God Almighty who persuades the mind and relaxes it, and the second: the work that polishes the heart and soul with knowledge and saves it from distraction and negligence.